Деревья решений для индукции лингвистических правил - Олейник, А. А.; Гофман, Е. А. (Видавництво Львівської політехніки, 2011)
The problem of linguistic rules induction is considered. A method of decision trees synthesis linguistic rules induction is suggested.
Keywords: деревья решений; искусственный интеллект; CART; индукция правил; лингвистические термы